Circulating CD14+ and CD14highCD16− classical monocytes are reduced in patients with signs of plaque neovascularization in the carotid artery. (December 2016) - Ammirati, Enrico; Moroni, Francesco; Magnoni, Marco; Di Terlizzi, Simona; Villa, Chiara; Sizzano, Federico; Palini, Alessio; Garlaschelli, Katia; Tripiciano, Fernanda; Scotti, Isabella; Catapano, Alberico Luigi; Manfredi, Angelo A.; et al.
Abstract: Background and aims: Monocytes are known to play a key role in the initiation and progression of atherosclerosis and contribute to plaque destabilization through the generation of signals that promote inflammation and neoangiogenesis. In humans, studies investigating the features of circulating monocytes in advanced atherosclerotic lesions are lacking. Methods: Patients (mean age 69 years, 56% males) with intermediate asymptomatic carotid stenosis (40–70% in diameter) were evaluated for maximal stenosis in common carotid artery, carotid bulb and internal carotid artery, overall disease burden as estimated with total plaque area (TPA), greyscale and neovascularization in 244 advanced carotid plaques. Absolute counts of circulating CD14+ monocytes, of classical (CD14 high CD16−), intermediate (CD14 high CD16+) and non-classical (CD14 low CD16+) monocytes and HLA-DR+ median fluorescence intensity for each subset were evaluated with flow cytometry. Results: No correlation was found between monocytes and overall atherosclerotic burden, nor with high sensitivity C-reactive protein (hsCRP) or interleukin-6 (IL-6). In contrast, plaque signs of neovascularization were associated with significantly lower counts of circulating CD14+ monocytes (297 versus 350 cells/mm 3, p = 0.039) and of classical monocytes (255 versus 310 cells/mm 3, p = 0.029). Conclusions: Neovascularized atherosclerotic lesions selectively associate with lower blood levels of CD14+ and CD14 high CD16− monocytes independently of systemic inflammatory activity, as indicated by normal hsCRP levels. Whether the reduction of circulating CD14+ and CD14 high CD16− monocytes is due to a potential redistribution of these cell types into active lesions remains to be explored. Highlights: Monocytes subsets and contrast-enhanced ultrasound (CEUS) evidence of carotid plaque neovassels relation were assessed. Activated total and classical monocytes are reduced in patients with neovessels. No association was found between plaque neovessels and inflammation biomarkers.